Pengaruh E-WOM pada TikTok terhadap Purchase Intention Produk Rose All Day - Bryant, Vanessa; Panggabean, Sheli Angraini; Widjojo, Handyanto; Rahman, Fathony (Kajian Branding Indonesia, 2025)
E-WOM (Electronic Word of Mouth) is an online marketing technique that is spread through verbal communication in the digital world. TikTok is one of the most widely used platforms for E-WOM. This research aims to examine the influence of E-WOM on the purchase intention of Rose All Day products. To understand the influence of E-WOM, we applied the IAM (Information Adoption Model) by Sussman and Siegel (2003) and IACM (Information Acceptance Model) by Erkan and Evans (2016). This research adopts a quantitative approach with purposive sampling technique, utilizing the AMOS-SEM software to analyze data. Researchers conducted a survey of 223 samples of Rose All Day’s followers on TikTok. The results show that there is a positive influence between argument quality and source credibility towards information usefulness, information usefulness towards information adoption, as well as information adoption positively influences purchase intention. Based on these findings, several suggestions are made for Rose All Day’s management in understanding the role and benefits of argument quality, review quality, source credibility and needs of information of E-WOM on TikTok towards information usefulness, and encourage consumers to spread positive word-of-mouth to increase purchase intention.